Magnetoelectric synergy strategy for superior iron disulfide anode. Issue 5 (13th February 2023) - Xiao, Yaoyao; Liu, Yihui; Liu, Bingbing; Qi, Zhenguo; Zhang, Youbin; Liu, Fusheng; Qin, Guohui
Abstract : The magnetic FeS2 /C@VS2 heterostructure with abundant edge sites and dangling sites was designed to achieve highly reversible sodium storage. Abstract : Iron disulfide is one of the most promising anode candidates for sodium ion batteries (SIBs). Nevertheless, sluggish kinetic behavior, huge volumetric variations, and poor interface compatibility cause the growth of sodium dendrites, which seriously limit further applications of SIBs. Herein, a core–shell flower-like FeS2 /C@VS2 heterojunction, with enriched edge sites, dangling bonds, and extraordinary interface compatibility, was fabricated for SIBs. The inner core–shell structure and doped carbon matrix create a stable nanostructure, and effectively reduce volume expansion during repeated Na + plating/stripping. Comprehensive experimental characteristics and theoretical calculations evidence that the adsorption energy increases and the barrier energy decreases for Na + diffusion of the hybrid composite, with excellent interface compatibility, indicating that the fast Na + diffusion process results from the superior kinetic behavior. The driving force of the magnetohydrodynamic (MHD) effect can redistribute the Na + flux well, thus inhibiting the growth of sodium dendrites and improving the structural and electrochemical stability. Moreover, the V sites of FeS2 /C@VS2 promote insertion of Na + ion, while the electron-rich Fe sites enhance the conversion reaction kinetics. The obtained FeS2 /C@VS2 exhibits excellent Na + storage properties, high reversible capacity (589 mA h g −1 at 0.05 A g −1 ), and excellent cycle stability (460 mA h g −1 after 500 cycles at 1 A g −1 ). This protocol for constructing a synergistic division-of-labor cooperative system, using the magnetoelectric strategy and interfacial interactions, provides a strategy for accelerating the insertion/conversion reaction involved in transition metal sulfides in SIBs.